Diagnosis of pulmonary Scedosporium apiospermum infection from bronchoalveolar lavage fluid by metagenomic next-generation sequencing in an immunocompetent female patient with normal lung structure: a case report and literature review - Jingru Han; Lifang Liang; Qingshu Li; Ruihang Deng; Chenyang Liu; Xuekai Wu; Yuxin Zhang; Ruowen Zhang; Haiyun Dai (BMC Infectious Diseases, 2024)
Abstract Background Scedosporium apiospermum (S. apiospermum) belongs to the asexual form of Pseudallescheria boydii and is widely distributed in various environments. S. apiospermum is the most common cause of pulmonary infection; however, invasive diseases are usually limited to patients with immunodeficiency. Case presentation A 54-year-old Chinese non-smoker female patient with normal lung structure and function was diagnosed with pulmonary S. apiospermum infection by metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF). The patient was admitted to the hospital after experiencing intermittent right chest pain for 8 months. Chest computed tomography revealed a thick-walled cavity in the upper lobe of the right lung with mild soft tissue enhancement. S. apiospermum was detected by the mNGS of BALF, and DNA sequencing reads were 426. Following treatment with voriconazole (300 mg q12h d1; 200 mg q12h d2-d20), there was no improvement in chest imaging, and a thoracoscopic right upper lobectomy was performed. Postoperative pathological results observed silver staining and PAS-positive oval spores in the alveolar septum, bronchiolar wall, and alveolar cavity, and fungal infection was considered. The patient’s symptoms improved; the patient continued voriconazole for 2 months after surgery. No signs of radiological progression or recurrence were observed at the 10-month postoperative follow-up. Conclusion This case report indicates that S. apiospermum infection can occur in immunocompetent individuals and that the mNGS of BALF can assist in its diagnosis and treatment. Additionally, the combined therapy of antifungal drugs and surgery exhibits a potent effect on the disease.